2021
DOI: 10.1186/s12929-021-00749-z
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Downregulating lncRNA NEAT1 induces proliferation and represses apoptosis of ovarian granulosa cells in polycystic ovary syndrome via microRNA-381/IGF1 axis

Abstract: Objective Researchers have revealed the combined functions of long noncoding RNAs (lncRNAs) and microRNA (miRNAs) in polycystic ovary syndrome (PCOS). This study aimed to understand the role of nuclear-enriched abundant transcript 1 (NEAT1) and miR-381 involving insulin-like growth factor 1 (IGF1) in PCOS. Methods PCOS rat model was established by dehydroepiandrosterone induction. NEAT1, miR-381 and IGF1 expression in ovarian granulosa cells of PCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…OC is responsible for the leading cause of cancer-related deaths, with approximately 45% of five-year overall survival [ 27 , 28 ]. As reported in numerous studies, lncRNAs have been involved in cell growth, apoptosis, invasion, and metastasis of malignant tumor including OC [ 29 , 30 ] and produced an effect on the overall survival [ 31 ]. For instance, the lncRNA-mediated m6A regulation was reported to be associated with OC remission and deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…OC is responsible for the leading cause of cancer-related deaths, with approximately 45% of five-year overall survival [ 27 , 28 ]. As reported in numerous studies, lncRNAs have been involved in cell growth, apoptosis, invasion, and metastasis of malignant tumor including OC [ 29 , 30 ] and produced an effect on the overall survival [ 31 ]. For instance, the lncRNA-mediated m6A regulation was reported to be associated with OC remission and deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…And Yang et al showed that silencing the lncRNA UCA1 could inhibit the development of PCOS via regulating PI3K-AKT signaling pathway ( 44 ). Moreover, downregulating lncRNA NEAT1 could also inhibit apoptosis and improve cell proliferation of ovarian GCs via microRNA-381/IGF1 axis, which associated with improved pathological process of PCOS ( 45 ). And our results exhibited that the expression of lncRNA was also significantly correlated with abnormal hormone, plasma metabolites level and embryo quality: NONHSAT101926.2 was mainly related to lipid metabolism, NONHSAT227177.1 and NONHSAT230904.1 were mainly related to plasma steroid hormones, NONHSAT010538.2 was positively associated with the LH/FSH ratio, while ENST00000607307 and NONHSAT191377.1 were related to plasma steroid hormones and follicle development.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA from U251 and T98G cells was extracted using TRIzol reagent (Invitrogen, CA) as previously described [ 15 ]. qRT-PCR was performed using SYBR Green Premix Ex Taq (TaKaRa) according to the manufacturer’s recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…Protein samples preparation and western blot analysis were performed as previously described [ 15 ]. Briefly, glioma cells were lysed using RIPA lysis buffer supplemented with protease inhibitors.…”
Section: Methodsmentioning
confidence: 99%